2015
DOI: 10.5455/ijmsph.2015.11032015202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenugreek seeds on glycemia and dyslipidemia in patients with type 2 diabetes mellitus

Abstract: effects compared to chemical medicines. Many antidiabetic products of herbal origin are available in India. Hence, we planned to evaluate effect of one of them, that is, fenugreek (Trigonella foenumgraecum). These seeds have been shown to have an effect on cholesterol and blood sugar. [1] Fenugreek seeds are used for the treatment of diabetes mellitus (DM) in many parts of the world including India. [2-4] These seeds are high in soluble fibers, saponins, trigonelline, diosgenin, and 4-hydroxy leucine. [5,6] So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In our meta‐analysis of 15 RCTs (11 with control and 4 without control; Abdel‐Barry et al, 2000; Chevassus et al, 2009; Fedacko et al, 2016; Gaddam et al, 2009; Geberemeskel et al, 2019; Gupta & Gupta, 2001; Kandhare et al, 2018; Kassaian et al, 2009; Kumar et al, 2015; Maheshwari et al, 2017; Moosa et al, 2006; Najdi et al, 2019; Rafraf et al, 2014; Sfar et al, 2018; Yousefi et al, 2017), intake of fenugreek resulted in a significant reduction in TC, TG, and LDL only in studies with control but not in uncontrolled studies. Our results showed that fenugreek consumption has significant positive effect on HDL elevation both in controlled and uncontrolled studies.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In our meta‐analysis of 15 RCTs (11 with control and 4 without control; Abdel‐Barry et al, 2000; Chevassus et al, 2009; Fedacko et al, 2016; Gaddam et al, 2009; Geberemeskel et al, 2019; Gupta & Gupta, 2001; Kandhare et al, 2018; Kassaian et al, 2009; Kumar et al, 2015; Maheshwari et al, 2017; Moosa et al, 2006; Najdi et al, 2019; Rafraf et al, 2014; Sfar et al, 2018; Yousefi et al, 2017), intake of fenugreek resulted in a significant reduction in TC, TG, and LDL only in studies with control but not in uncontrolled studies. Our results showed that fenugreek consumption has significant positive effect on HDL elevation both in controlled and uncontrolled studies.…”
Section: Discussionmentioning
confidence: 82%
“…Two articles one in Chinese (Shen, Li, Lu, Yu, & Zheng, 2013) and one published before 2000 (Bordia, Verma, & Srivastava, 1997) which did not meet our inclusion criteria were excluded. Finally only 15 articles were selected for meta‐analysis (11 controlled and four uncontrolled; Abdel‐Barry, Abdel‐Hassan, Jawad, & al‐Hakiem, 2000; Chevassus et al, 2009; Fedacko et al, 2016; Gaddam et al, 2009; Geberemeskel, Debebe, & Nguse, 2019; Gupta & Gupta, 2001; Kandhare, Phadke, Mane, Thakurdesai, & Bhaskaran, 2018; Kassaian, Azadbakht, Forghani, & Amini, 2009; Kumar, Kumar, Datta, & Bandyopadhyay, 2015; Maheshwari et al, 2017; Moosa et al, 2006; Najdi, Hagras, Kamel, & Magadmi, 2019; Rafraf, Malekiyan, Asghari‐Jafarabadi, & Aliasgarzadeh, 2014; Sfar et al, 2018; Yousefi et al, 2017) involving 281 cases consumed fenugreek and 255 control cases in controlled group and 136 cases in uncontrolled group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HDL cholesterol levels in the patients showed a significant increase (p<0.001). 35 Fenugreek seeds lower the serum triglycerides, total cholesterol and LDL cholesterol. This is due to sapogenins, which increase biliary cholesterol excretion in turn leading to lowered cholesterol levels.…”
Section: Discussionmentioning
confidence: 98%